Long Term Government Debt, Financial Fragility and Sovereign Default Risk - Christiaan van der Kwaak; Sweder van Wijnbergen (Tinbergen Institute, 2013)
We analyze the interaction between bank rescues, financial fragility and sovereign debt discounts. We construct a model that contains balance sheet constrained financial intermediaries financing both capital expenditure of intermediate goods producers and government deficits. The financial intermediaries face the risk of a (partial) default of the government on its debt obligations. We analyse the impact of a financial crisis, first under full government credibility and then with an endogenous sovereign debt discount. The introduction of the default possibility does not have any impact IF all government debt is short term. Interest rates on debt reflect higher default probabilities, but because all debt is short term, bank balance sheets are unaffected and no further negative effects arise through the endogenous sovereign debt channel. But once long term government debt is introduced, the possibility of capital losses on bank balance sheets arises. Then outcomes significantly deteriorate compared to the short term debt only case. Higher interest rates on new debt lead to capital losses on banks' holding of existing long term government debt. The associated increase in credit tightness leads to a negative amplification effect, significantly increasing output losses and declines in investment after a financial crisis. This causes potentially conflicting macroeconomic effects of a debt financed recapitalization of banks. We investigate the case where the government announces a bank recapitalization to occur 4 quarters after announcement. Under the parameter values chosen, the positive effects from an anticipated capital injection dominate the effects of the associated increase in sovereign default risk.
Keywords: E44; E62; H30; 330; Financial Intermediation; Macrofinancial Fragility; Fiscal Policy; Sovereign Default Risk